Towards A Framework for Performance Management and Machine Learning in A Higher Education Institution - Dr. Priya J, Dr. Shaik Balkhis Banu, Dr. K. Suresh Kumar; Dr. Priyanka Rana, Mohammed Rizvi, Shailendra Kumar Rai (Journal of Informatics Education and Research, 2024)
Performance management is a process that helps an organisation to manage its performance. Therefore, there are three stages of performance management such as coaching, corrective action, and then termination. A proper performance management process is very important for the development of a higher education institute. Apart from that, machine learning is another important process that is based on software technology. Therefore, machine learning helps to predict the outcomes of learning. There are a total of four types of algorithms of machine learning such as unsupervised, supervised, semi-supervised, and reinforcement. Furthermore, the use of performance management helps to enhance the productivity of the students of higher education institutions. In addition to that, the use of machine learning in higher education institutions is also helpful to enhance the productivity of the students. As both of the processes are efficient to gain knowledge about several things, therefore it helps to enhance the productivity of the students of higher education institutions. On the other hand, the purpose of this particular research study is to create a framework for machine learning and performance management in a higher education institution. Therefore, the framework is efficient and effective to understand the concept of research topics. Furthermore, the Framework for machine learning and performance management will help the students of higher education institutions to understand the impacts of these processes on their productivity. Apart from that, the researcher has used several types of methods and techniques for collecting and analysing all the data about the particular research topic. Thus, the researcher has adopted secondary methods for gathering more information and data about the research topic. Along with that, the researcher has used qualitative techniques for analysing all the data in this particular research study.